Pengaruh Project Based Learning berbantuan Quizizz terhadap Hasil Belajar Siswa pada Mata Pelajaran Pemrograman Web dan Perangkat Bergerak di SMKN 2 Padang - Falda, Regina; Delianti, Vera Irma (Lembaga Yasin AlSys, 2025)
This study aims to examine the effect of the Project-Based Learning model assisted by Quizizz on student learning outcomes in the subject of Web and Mobile Device Programming at SMK Negeri 2 Padang. A quasi-experimental design was used, involving two sample classes: an experimental class implementing Project-Based Learning with Quizizz, and a control class using only Project-Based Learning. Data were collected through pre-test and post-test assessments, and analyzed using the Shapiro–Wilk normality test, F test for homogeneity, and independent t-test. The results showed a significant difference between the two groups, with the experimental class achieving a higher average post-test score of 78.0 compared to 71.76 in the control class. The t-test yielded a t-value of 2.570, exceeding the critical value of 1.668, with a significance level of 0.012 (< 0.05), confirming that the integration of Quizizz into Project-Based Learning has a positive effect on student learning outcomes. These findings affirm the effectiveness of this learning model and support its use as a viable alternative to enhance the quality of education in vocational schools and other educational institutions.